Understanding burnout among operating room nurses: a qualitative study - Li, Yufang; Xiang, Dan; Jiang, Yun; Gu, Su (Frontiers in Public Health, 2025)
ObjectiveThis study aimed to explore the lived experiences of job burnout among operating room nurses and to provide an evidence-based foundation for developing targeted nursing interventions to mitigate job burnout in this population.MethodA purposive sampling method, guided by the principle of maximum variation, was employed to recruit 14 operating room nurses from a tertiary Grade A hospital in Anhui Province in January 2025. A phenomenological research approach was adopted, utilizing semi-structured interviews for data collection. Interview data were analyzed using Colaizzi’s seven-step method. Data collection continued until thematic saturation was achieved—meaning no new themes emerged in subsequent interviews.ResultsEight major themes and thirteen subthemes were extracted. Among these, five major themes were identified as factors contributing to occupational burnout among operating room nurses, while three major themes were related to coping strategies. Specifically, the findings indicated that occupational burnout among nurses was closely associated with excessive workload, insufficient emotional support, career development stagnation, and the high-pressure dynamics of healthcare relationships. Nurses commonly reported a lack of professional fulfillment and an absence of effective strategies to cope with emotional exhaustion in their work.ConclusionBurnout among operating room nurses results from the interplay of multiple factors. This study identifies key mechanisms underlying burnout in nurses working in high-pressure environments, emphasizing the importance of improving organizational support, optimizing nurse-physician communication, and clarifying career development pathways. These findings provide a theoretical basis for the development of targeted nursing management strategies and interventions, which may effectively alleviate nurse burnout and enhance both nursing quality and team stability.